"Diaspora Indonesia dan Gamelan Jawa di Inggris: Dampak Relokasi Tradisi terhadap Pembentukan Identitas dan Komunitas" - Leilani Hermiasih (Jurnal Kajian Seni, 2016)
This study has examined the various realms of diasporic gamelan musical communitiesin Britain. While being displaced from their homeland, these members of the Indonesiancommunity reinforce their national identity through gamelan music making activities in therealm of a community of practice. These practices involve a constant interplay betweentheir participation in learning the music and reifi cation in performing it for other membersof the diaspora, as well as the British public. Within both realms of practice, as agentsof their own identity and community formation, these migrants practice authenticationthrough the establishment of claims on tradition and modernity—as this phenomenonis a part of the greater phenomena of deterritorialization, cultural displacement, andglobalization.